1994
DOI: 10.4319/lo.1994.39.3.0632
|View full text |Cite
|
Sign up to set email alerts
|

Natural versus human-caused variability of water clarity in the Southern California Bight

Abstract: This paper examines the spatial and temporal variability of two optical properties (percent transmissivity and Secchi disk depth) measured near three areas in the Southern California Bight in which strong human influence, in the form of sewage discharge, is present. Fifteen years of data collected monthly at test and control stations were examined by time-series and other statistical analyses. By comparing the variability of these properties between the three areas (50-200 km apart) and within areas with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
8
2
Order By: Relevance
“…The few reports of increased Secchi depths were associated with bioremediation or efforts to reduce untreated sewage outfall. For example, Secchi depths increased at 0.05 m/year in Narragansett Bay, Rhode Island, coincident with reductions in anthropogenic total suspended solids (Borkman and Smayda, 1998), as at one of several sampled sites in the Southern California Bight (Convers and McGowan, 1994). Our measures show a much more rapid change in Secchi depths than these previous studies.…”
Section: Long-term Trend In Secchi Depthscontrasting
confidence: 55%
“…The few reports of increased Secchi depths were associated with bioremediation or efforts to reduce untreated sewage outfall. For example, Secchi depths increased at 0.05 m/year in Narragansett Bay, Rhode Island, coincident with reductions in anthropogenic total suspended solids (Borkman and Smayda, 1998), as at one of several sampled sites in the Southern California Bight (Convers and McGowan, 1994). Our measures show a much more rapid change in Secchi depths than these previous studies.…”
Section: Long-term Trend In Secchi Depthscontrasting
confidence: 55%
“…In some enclosed coastal seas, long-term reduction in water clarity has been connected to human-caused nutrient emissions (Mankovsky et al 1996;Sanden and Hå kansson 1996). Conversi and McGowan (1994) examined the natural vs. human-caused variability of water clarity close to the coast in the Southern California Bight with particular emphasis on sewage discharges. Although their results did not provide a totally unambiguous picture, they indicated that most of the water clarity variability was driven by bight-wide natural phenomena.…”
Section: Forcing Parametersmentioning
confidence: 99%
“…These methods provided us with a methodical approach to the analysis of ecological time series that has helped reveal causes of temporal variability in a number of different systems. Note that Secchi depth spatial structure can also be analyzed to reveal underlying mechanisms (Conversi and McGowan 1994), but our data have confined us largely to the time domain.…”
Section: S C ϩ Kmentioning
confidence: 99%